Charlotte Blensdorf MacJannet with visitors to the Priory, ca. 1962 - MacJannet, Donald (Tufts Archival Research Center, 2005)
2x2 color slide; taken from MS024/007-072 - "Donald MacJannet slides from trips and home, ca. 1960-1980"